URGENSI SISTEM PENJAMINAN MUTU INTERNAL & EKSTERNAL DALAM MENINGKATKAN MUTU PERGURUAN TINGGI - Yoga Budi Bhakti; Achmad Ridwan; Riyadi (Jurnal Penjaminan Mutu, 2022)
Higher education quality assurance is aimed at quality education. Universities must systematically carry out the quality assurance process through the Higher Education Quality Assurance System and refer to the National Higher Education Standards. There are two quality assurance systems in higher education, namely; internal quality assurance and external quality assurance. The internal quality assurance system is a systemic activity of quality assurance of higher education by each university autonomously to control and improve the implementation of higher education in a planned and sustainable manner. Meanwhile, the external quality assurance system is an assessment activity carried out by outside units to determine the feasibility of universities. This study aims to fully describe two main things in the quality assurance system in higher education institutions, namely; internal quality assurance and external quality assurance. In obtaining this research data, a qualitative approach to the type of library research is used, by collecting data from books, journals and articles. Data analysis is carried out using content analysis. The results of the study found that: First, internal quality assurance includes: policies and procedures for quality assurance; approval, monitoring and periodic review of programs and awards; student assessment, quality assurance of teaching staff/lecturers; learning resources and student support; information systems; public information. Second, external quality assurance, namely: the use of procedures; process development; criteria for decisions; process in accordance with the purpose; reporting; follow-up procedures; periodic review of the implementation; and system-wide analysis